A Review Paper: Digital Image Filtering Processing - Al-Taie, Rana (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
Nowadays, visual information is increasingly sent in the form of digital images, making the identification of noisy data a common challenge in many research and application domains. Many noise reduction techniques have been developed in the contemporary era to remove noise while preserving image information. The task of eliminating noise from an original image remains a difficult one for researchers. The primary focus of this study is on picture denoising and filtering. For performing a comparative examination of existing denoising techniques, such as linear and nonlinear filters. salt, pepper noise, Gaussian noise, and speckle noise are examples of different noise models. PSNR of color images provides a quantity measure of comparison.